A sex-based analysis of complete blood count features during acute, untreated Lyme disease - Rebman, Alison W.; Yang, Ting; Zenilman, Jonathan M.; Soloski, Mark J.; Aucott, John N. (Frontiers in Medicine, 2024)
Introduction Although lymphopenia has been described in acute Lyme disease (LD), the complete blood count (CBC) has not been comprehensively examined, nor have sex-based analyses been conducted. We analyzed CBC values and identified sex-based trends among patients with early LD by comparing both to controls without a history of LD and to patients’ pre-morbid values. Methods We enrolled participants from the Mid-Atlantic US with diagnostic erythema migrans and controls with no history of LD. CBC results were obtained, and patient information was recorded using standardized instruments. We also calculated a neutrophil-to-lymphocyte ratio (NLR). We used linear regression to test that CBC results would differ (a) between antibiotic-naive patients with early LD and controls and (b) by measures of acute disease severity. We also performed stratified analyses to assess sex-based differences. Results In total, 236 antibiotic-naive patients with early LD had significantly lower lymphocytes (β = −0.34, p < 0.001) and significantly higher monocytes (β = 0.09, p = 0.002) and NLRs (β = 0.99, p < 0.001) than 61 controls in adjusted analyses. Lymphocytes, monocytes, and NLRs also changed significantly from pre-morbid to acute LD (p < 0.001 for all). Only the NLR was consistently significantly associated with disease severity. A higher proportion of male patients with early LD had acute lymphopenia than female patients with early LD (31.93% vs. 19.66%, p = 0.03); this difference was not present among controls. Conclusion The presence of lymphopenia and the absence of an elevated total white blood cell count make LD an important diagnostic consideration in patients presenting with undiagnosed infectious syndromes in endemic regions. This may be especially true for male patients.